Mental illness and comorbidities, aspects of initial evaluation - Mayor, M. S.; Pestana, M. H.; Reis, G.; Santos, J. M. (International Journal of Statistics and Applications, 2015)
Mental Illness is a public problem in western societies. Recent reports say that the most frequent conditions of psychiatric hospitalization are related to elderly, over 65 years old, diagnosed with dementia, other organic disorders and depression. And we are seeing increasingly in episodes of urgency, consumption of psychoactive drugs, which can foster the emergence of other comorbidities. The aim of this study was to characterize from a socio-demographic, clinical and functional point of view, older people who staged an emergency episode in a psychiatric hospital. This is a cross-sectional, descriptive and correlational study. The sample consisted of 99 elderly people involved in a psychiatric emergency episode in the biennium 2013/2014 and data were collected from the initial evaluation form (IE). Results: People with dementia have more associated diseases than others with other mental Illnesses. Some are at higher risk for potential episodes of falls and loss of functionality and associated factors. Conclusion. More cognitive and functional impairment, evidenced in the functional dependency cycle. The quality of care in later age, requires a multidimensional and interdisciplinary approach. Initial assessment must be complete and holistic in order to give the best care.